PENGARUH EFEKTIFITAS PENERAPAN SISTEM INFORMASI MANAJEMEN KEUANGAN DAERAH (SIMDA) TERHADAP PENINGKATAN KINERJA PEGAWAI DI KANTOR BADAN PENGELOLA KEUANGAN DAN ASET DAERAH (BPKAD) KABUPATEN OGAN ILIR - Tutik Pebrianti; Anton Trianto (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2021)
This study aims to analyze the effect of the effectiveness of the implementation of the Regional Management Information System (SIMDA) program on improving employee performance at the Regional Financial and Asset Management Agency (BPKAD) of Ogan Ilir Regency. The sample used is purposive sampling, namely as many as 14 employees who are in direct contact with the use of SIMDA. The data used is secondary data. Methods of data collection by using a questionnaire. The research was conducted in May 2021 at the BPKAD Ogan Ilir Office. The analysis technique used is Simple Linear Regression Analysis. The results obtained are that the implementation of SIMDA at BPKAD Ogan Ili can be considered to have been running quite effectively. Based on the results of regression estimation and hypothesis testing through t-test, it was found that the effectiveness of SIMDA implementation has a positive and significant effect on improving the performance of BPKAD Ogan Ilir employees.